Konsep Dasar Masyarakat Dalam Persfektif Ibnu Khaldun - Elen Safitri; Kartina Anggraini Nasution; Khairan Syaputra Tarigan (IAI Nasional Laa Roiba Bogor, 2024)
Ibn Khaldun was an Islamic scientist and scientist whose thoughts and ideas were considered reliable in his time. His ideas about society as outlined in his work entitled